DOES A ACCOUNTING LITERACY, FINANCIAL TECHNOLOGY, RISK LEVEL AND LOCUS OF CONTROL ON INVESTMENT DECISIONS AMONG Z GENERATION? - Ugli, Teshaev Jahongir Isomiddin; Denny Andriana; R Nelly Nur Apandi (Bajang Institute, 2025)
Accounting literacy, financial technology, risk level, and locus of control are often cited as key factors influencing individual investment behavior. In this study, we investigate the impact of these variables on investment decision-making among z generation who study at Universitas Pendidikan Indonesia. A total of 44 respondents participated Using a quantitative approach and multiple regression analysis, the findings reveal that risk level significantly influences students' investment decisions, while accounting literacy shows a borderline significance. Conversely, financial technology usage and locus of control do not show a significant relationship with investment decisions. These results suggest that z generation are more driven by their perception of financial risk when making investments rather than external technology tools or internal control beliefs. The study highlights the need for enhancing financial education programs that address risk awareness to improve investment behaviors among z generation.